Patterns of needs among Iraqi families caring for children with autism spectrum disorder: a cross-sectional study - Kadhim Nayyef, Nadia; Mohammed Jasim, Shatha; Lami, Faris; Abbas Jaber, Osamah; Dehghan Nayeri, Nahid; Shafiee Sabet, Mahdi; Al-Gburi, Ghaith (Frontiers in Psychiatry, 2025)
ObjectiveChildren with autism spectrum disorder (ASD) often require significant family support to carry out their daily activities. Assessing the needs of these families is important to optimize the use of the limited financial and professional resources available to them. This study aims to evaluate the needs of Iraqi families who care for children with ASD in various area and explore how these needs are related to the characteristics of child.MethodParents of children with ASD attending Al-Subtain Academy for Autism and Neurodevelopmental Disorders were included in a cross-sectional survey between January 20, 2024, and September 9, 2024. A structured standardized questionnaire was utilized to evaluate family needs in four domains: the need for information, explaining to others, childcare needs, and professional support.Result249 parents were interviewed, consisting of 196 (78.7%) mothers and 53 (21.3%) fathers. Over 80% of parents required support in finding information, particularly information regarding services available for their children. With in their perspective domains, support in finding reading materials about similar families and talking to them were the most requested needs, being mentioned by 40.6% and 18.1% of parents, respectively. Parents of children with comorbidities reported higher childcare and professional support needs, presumably due to a higher need for respite care and more time spent talking to teacher and therapists.ConclusionParents should be provided with better access to information, particularly regarding services available for their children, and more opportunities to communicate with teachers, therapists, and similar families to reduce social isolation.